Various inputs applied for growing sweet potato in the tidal swamp area of south Borneo of Indonesia (International Journal of Agricultural Research, Innovation and Technology, 2021)
In South Borneo, sweet potato baking is very good market and has to be shipped from Java for fulfilling the demand of the people. Preparation of sweet potato as additional food is only simple by put in oven, so it is sold fresh from the oven. In 2015, description of area mainly physical and chemical aspects were undertaken to provide adequately data. Analysis of soil sample was done for the parameters of pH, C organic as well as N, P and K. Based on this analysis, the treatment was designed based on practical work. Apex vine cutting of several sweet potato varieties were taken from ILETRI to Borneo during 2016 and 2017. In 2017, two varieties were used as the main plot, and five inputs were determined as subplot. Therefore, ten combination treatments were laid down in three replications, in the plot size of 6.0 m x 5.0 m. Planting distance of sweet potato was 100 cm x 25 cm. During 2017, planting was done at February and harvesting was undertaken on July. Growth and yield components were analyzed by statistical procedure by using MSTATC. Statistical analysis indicated that there was not significantly affected by interaction between variety and agronomic inputs as well. However, both main and subplot were separately affected growth and yield. ILETRI variety Beta3 gave better yield with agronomic input1 able to obtain 15.39 t ha-1. However, the increase of agronomic input did not follow the increase of tuber yield.Int. J. Agril. Res. Innov. Tech. 10(2): 29-34, December 2020